PENGARUH PENGGUNAAN MEDIA INTERAKTIF CANVA BERBANTUAN EDUCAPLAY TERHADAP HASIL BELAJAR BAHASA INDONESIA MATERI SINONIM DAN ANTONIM SISWA KELAS V SD NEGERI 1 BEUREUNUEN - Wilzani, Syilmi; Mislinawati; Hasniyati; Kurniawati, Rizki (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Synonym and antonym material in Indonesian language learning still shows low student learning outcomes. This condition is influenced by the use of less varied learning media, causing students to be less active and not fully understand the concepts. This study aims to determine the effect of using interactive Canva media assisted by Educaplay on the Indonesian language learning outcomes of fifth-grade students at SD Negeri 1 Beureunuen. The study employed a quantitative approach using a Quasi-Experimental Design with a Non-Equivalent Control Group Design. The sample consisted of 45 students, including 23 students from class VA as the experimental group and 21 students from class VB as the control group, selected through purposive sampling. Data were collected using a multiple-choice objective test consisting of 20 questions administered during the pre-test and post-test. Data analysis included the N-Gain test, normality test, homogeneity test, and independent sample t-test using SPSS. The results showed that the average score of the experimental class increased from 59.3 to 85.4 with an N-Gain value of 0.645 (moderate category), while the control class increased from 48 to 63.8 with an N-Gain value of 0.287 (low category). The independent sample t-test results showed a significance value (2-tailed) < 0.05, indicating that the use of interactive Canva media assisted by Educaplay has a significant effect on students’ Indonesian language learning outcomes. Keywords: Canva interactive media, Educaplay, learning outcomes, synonyms and antonyms.